Stone Statues in Galuut soum, Bayankhongor aimag (Studia Archaeologica, 2026)
During the 2018 and 2019 field seasons, the Mongolian-Chinese Joint Archaeological Expedition identified six previously unrecorded Old Turkic stone statues and numerous ritual enclosures in the territory of Galuut soum, Bayankhongor aimag, in the southwestern Khangai Mountains. Together with four stone statues previously documented from the same area, the total number of known examples in the region now stands at ten. Drawing on the descriptions of these ten monuments, this article discusses their regional characteristics, iconographic features, and chronological. In the course of the same survey, several sites bearing Old Turkic runic inscriptions and tamga symbols were also identified and brought into scholarly discussion. Studies of these runic inscriptions suggest that the area may have been situated along an ancient route of communication. Moreover, based on the inscriptions and tamga symbols discovered in the Baidrag River basin, not far from the Galuut stone statues, some scholars have proposed that this region may once have belonged to the Basmil tribe during the Old Turkic period. In this regard, the stone statues of Galuut soum constitute valuable evidence for investigating the history of the Basmils-frequently mentioned in historical sources as a powerful tribe in the final period of the Turkic Khaganate-as well as that of their neighboring groups.Баянхонгор аймгийн Галуут сумын нутагт буй хүн чулуудын тухайХураангуй: 2018, 2019 онд Монгол-Хятадын хамтарсан археологийн хээрийн шинжилгээний анги Хангайн нурууны баруун өмнөд хэсэгт орших Баянхонгор аймгийн Галуут сумын нутагт эртний түрэгийн үеийн 6 хүн чулуу, олон тахилын онгон шинээр илрүүлсэн билээ. Үүнээс гадна тухайн бүс нутагт урьд нь судалгааны эргэлтэд орсон 4 хүн чулууг нэмбэл нийт 10 хүн чулуу болно. Бид энэ 10 чулууны тодорхойлолт дээр дулдуйдаж бүс нутгийн онцлог, дүр дүрсэлбэр, он цагийн асуудлыг хөндлөө. Мөн уг хайгуул судалгааны үеэр түрэгийн руни бичгийн дурсгал, тамга тэмдэг бүхий дурсгалт газруудыг илрүүлж судалгааны эргэлтэд өмнө оруулсан юм. Руни бичгийн судалгааны дүнд эртний зам харилцааны газар бололтой гэж үзсэн. Мөн судлаачид Галуутын хүн чулуудаас холгүй Байдраг голын саваас илрүүлсэн бичээс, тамга тэмдгүүдийг судлаад эртний түрэгийн үеийн Басмыл аймгийн нутаг байж болох юм хэмээн таамаг дэвшүүлсэн байдаг. Ямартаа ч Галуут сумын нутагт буй хүн чулууд нь Түрэгийн хаант улсын сүүл үед хүчирхэгжсэн нь сурвалжид олонтой дурдагддаг Басмыл аймаг хийгээд түүний хөрш аймгуудыг түүхийг судлах сонирхолтой хэрэглэгдэхүүн болох нь дамжиггүй юм.      Түлхүүр үг: Баянхонгор, Хүн чулуу, Галуут, Түрэгийн үе, Басмыл аймаг